The long-term effect of elevated CO₂ on grassland biomass production - Asary, Melanie (Department of Biological Sciences, 2017)
This study investigates the influence of elevated CO₂ on grassland biomass production at a naturally elevated CO₂ spring situated on the Bongwan gas fault in Natal. The effect of elevated CO₂ on monocotyledenous (C₄) and dicotyledenous (C₃) above ground plant biomass production and their dominance patterns along a CO₂ gradient were studied. Three 7x7m plots were located 18m, 39m and 73m away from the elevated CO₂ spring. The 18m site was the experimental site, while the other two sites were the controls. The primary focus of the study was to determine the biomass production of monocotyledenous and dicotyledenous plants at the above-mentioned distance from the spring. However, to ascertain possible factors that could influence the increase in biomass production with distance from the CO₂ source, plant nutrient analyses (N and P), soil moisture contents (which could have an effect on plant wateruse efficiency) and carbon isotope discrimination values were determined at the three sites. The results show that elevated CO₂ had a significant effect on the monocotyledenous dry matter production, but had no significant effect on any of the other plants or soil. It was also shown that elevated CO₂ increased the soil water retention capacity as one moves toward the spring, however this result is not confirmed.